Semi-Trusted Authentication for Health Data in Cloud - M, Rajeswari; asmine.P, Anjelin Lilly J; Komaladevi, V.; Monika, K. (IJRDO -Journal of Computer Science Engineering, 2015)
Cloud-assisted health monitoring, which applies the widespread mobile communications and cloud computing technologies to provide feedback decision support, has been considered as a activist approach to improving the quality of healthcare service while lowering the healthcare cost. Unfortunately, it also poses a serious risk on both clients’ privacy and intellectual property of monitoring service providers, which could discourage the wide adoption of Health technology. This project is to address this important problem and design a cloud-assisted privacy preserving health monitoring system to protect the privacy of the involved parties and their data. Moreover, the outsourcing decryption technique and a newly proposed key private proxy re encryption are adapted to shift the computational complexity of the involved parties to the cloud without compromising clients’ privacy and service providers’ intellectual property. Finally, our security and performance analysis demonstrates the effectiveness of our proposed design. Proving secure and performance analysis demonstrates the effectiveness in cloud environment